Event-Related Potential Effects of Object Repetition Depend on Attention and Part-Whole Configuration - Gosling, Angela; Thoma, Volker; de Fockert, Jan W.; Richardson-Klavehn, Alan (Frontiers in Human Neuroscience, 2016)
The effects of spatial attention and part-whole configuration on recognition of repeated objects were investigated with behavioral and event-related potential (ERP) measures. Short-term repetition effects were measured for probe objects as a function of whether a preceding prime object was shown as an intact image or coarsely scrambled (split into two halves) and whether or not it had been attended during the prime display. In line with previous behavioral experiments, priming effects were observed from both intact and split primes for attended objects, but only from intact (repeated same-view) objects when they were unattended. These behavioral results were reflected in ERP waveforms at occipital-temporal locations as more negative-going deflections for repeated items in the time window between 220 and 300 ms after probe onset (N250r). Attended intact images showed generally more enhanced repetition effects than split ones. Unattended images showed repetition effects only when presented in an intact configuration, and this finding was limited to the right-hemisphere electrodes. Repetition effects in earlier (before 200 ms) time-windows were limited to attended conditions at occipito-temporal sites (N1), a component linked to the encoding of object structure, while repetition effects at central locations during the same time window (P150) were found only from objects repeated in the same intact configuration—both previously attended and unattended probe objects. The data indicate that view-generalization is mediated by a combination of analytic (part-based) representations and automatic view-dependent representations.